EPISTEMOLOGI AL-ASRAM: DALAM KITAB NA>SIKH AL-HADI>S| WA MANSU>KHUH - Hakim, Nurul (IAIN Ponorogo, 2019)
Abstract: Research on the hadith will never run out. From ancient times until now the tradition has always attracted the interest of researchers to examine it. If the early days, hadith criticism is often intended to get the quality of hadith (sahi>h, hasan, andda?i>f), then in the next development the purpose of the study of hadith cannot be limited to that, but already must be broadened for the purpose of understanding and practice. In this case, various methods of criticism of the tradition of hadith emerged. One method of criticism that scholars have known from the past to the present is the